BAFopathies’ DNA methylation epi-signatures demonstrate diagnostic utility and functional continuum of Coffin–Siris and Nicolaides–Baraitser syndromes - Erfan Aref-Eshghi (Nature Portfolio, 2018)
Mutations in genes encoding subunits of the BAF complex can cause Coffin–Siris and Nicolaides–Baraitser syndromes. Here the authors identify overlapping DNA methylation signatures in individuals with subtypes of these two syndromes that suggest a functional link and can be used to diagnose subjects with unclear clinical presentations.